Analisis Pengaruh Total Asset dan Hasil Investasi Terhadap Laba Perusahaan Asuransi Jiwa Syariah di Indonesia Periode 2015-2020 - Quraniyah, Fike; Rahmani, Nur Ahmadi Bi; Inayah, Nurul (Ikatan Da'i Indonesia, 2023)
This study aims to determine the effect of total assets and investment returns on profits of Islamic life insurance companies in Indonesia for the 2015-2020 period. This study consists of total assets and investment returns as independent variables and company profits as the dependent variable. company during the period 2015 to 2020. The results of the study showed that Total Assets (X1) showed an alpha coefficient of 5% (t-stat = 2.737>1.667) and prob. 0.008 < 0.05. Then the hypothesis is accepted, namely Total Assets has a significant effect on Net Profit at PT. Sharia Life Insurance Period 2015-2020. Investment returns (X2) show a 5% alpha coefficient (t-stat = 2.498>1.667) and prob. 0.015 < 0.05. Then the hypothesis is accepted, namely the investment return has a significant effect on net income at PT. Sharia Life Insurance Period 2015-2020. Total Assets (X1) and Investment Returns (X2) show a 5% alpha coefficient (t-stat = 4.807>2.76) and prob. 0.011 < 0.05. Then the hypothesis is accepted, namely Total Assets and Investment Returns have a significant effect on Net Profit at PT. Sharia Life Insurance Period 2015-2020.